Fetal brain response to worsening acidosis: an experimental study in a fetal sheep model of umbilical cord occlusions - Laure Lacan; Charles Garabedian; Julien De Jonckheere; Louise Ghesquiere; Laurent Storme; Dyuti Sharma; Sylvie Nguyen The Tich (Scientific Reports, 2023)
Abstract Perinatal anoxia remains an important public health problem as it can lead to hypoxic–ischaemic encephalopathy (HIE) and cause significant neonatal mortality and morbidity. The mechanisms of the fetal brain’s response to hypoxia are still unclear and current methods of in utero HIE prediction are not reliable. In this study, we directly analysed the brain response to hypoxia in fetal sheep using in utero EEG. Near-term fetal sheep were subjected to progressive hypoxia induced by repeated umbilical cord occlusions (UCO) at increasing frequency. EEG changes during and between UCO were analysed visually and quantitatively, and related with gasometric and haemodynamic data. EEG signal was suppressed during occlusions and progressively slowed between occlusions with the increasing severity of the occlusions. Per-occlusion EEG suppression correlated with per-occlusion bradycardia and increased blood pressure, whereas EEG slowing and amplitude decreases correlated with arterial hypotension and respiratory acidosis. The suppression of the EEG signal during cord occlusion, in parallel with cardiovascular adaptation could correspond to a rapid cerebral adaptation mechanism that may have a neuroprotective role. The progressive alteration of the signal with the severity of the occlusions would rather reflect the cerebral hypoperfusion due to the failure of the cardiovascular adaptation mechanisms.